Solubility of Aminotriethylene Glycol Functionalized Single Wall Carbon Nanotubes: A Density Functional Based Tight Binding Molecular Dynamics Study - Mananghaya, Michael Rivera (Archīum Ateneo, 2019)
Pristine CNTs are exemplary hydrophobic solutes; properly functionalized CNTs can be seen as hydrophilic ones. The solubility of aminotriethylene glycol (ATG) functionalized single walled carbon nanotubes (fSWCNTs) were examined using density functional based tight binding method. According to the dynamics study, the ATG-fSWCNTs interaction energies (IE) and diffusion coefficients (D) are diameter dependent. As the diameter of the (n,0) tube is incrementally increased, a distinguishable pattern is observed, specifically the IE of the ATG-fSWCNT in water is quite higher for n that is an integral multiple of three (n = 9,12,15) while the D is lower due to its π bonding structures. In general, the metallic ATG functionalized nanotube possess a higher IE and a much lower D in aqueous media. © 2019 Wiley Periodicals, Inc.